2021
DOI: 10.1136/jnnp-2020-323951
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microbleeds: from depiction to interpretation

Abstract: Cerebral microbleeds (CMBs) are defined as hypointense foci visible on T2*-weighted and susceptible-weighted MRI sequences. CMBs are increasingly recognised with the widespread use of MRI in healthy individuals as well as in the context of cerebrovascular disease or dementia. They can also be encountered in major critical medical conditions such as in patients requiring extracorporeal mechanical oxygenation. The advent of MRI-guided postmortem neuropathological examinations confirmed that, in the context of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 124 publications
2
77
1
Order By: Relevance
“…17,18 They showed that mixed CMBs were associated with cardiovascular mortality, while lobar CMBs were associated with stroke-speci c mortality compared to patients without CMBs; 17,18 these results correspond with the notion that mixed CMBs are considered to re ect hypertensive arteriopathy and, therefore, systemic vascular disease, while lobar CMBs are indicative of CAA and primarily restricted to the brain. 14 Although not provided in the literature, the strokes related to lobar CMB-associated mortality were probably intracerebral hemorrhage, a major clinical consequence of CAA. 19 Therefore, we postulated that causes of mortality in the CSVD type 4 in this study were primarily hemorrhagic strokes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…17,18 They showed that mixed CMBs were associated with cardiovascular mortality, while lobar CMBs were associated with stroke-speci c mortality compared to patients without CMBs; 17,18 these results correspond with the notion that mixed CMBs are considered to re ect hypertensive arteriopathy and, therefore, systemic vascular disease, while lobar CMBs are indicative of CAA and primarily restricted to the brain. 14 Although not provided in the literature, the strokes related to lobar CMB-associated mortality were probably intracerebral hemorrhage, a major clinical consequence of CAA. 19 Therefore, we postulated that causes of mortality in the CSVD type 4 in this study were primarily hemorrhagic strokes.…”
Section: Discussionmentioning
confidence: 98%
“…Bleeding CSVDs were further strati ed into different subtypes with CMBs of speci c topographic features that have distinct underlying microvasculopathy: strictly lobar CMBs considering as CAA and mixed CMBs as arteriosclerosis/lipohyalinosis microvasculopathy. 14,15 Regarding nonbleeding CSVDs, individuals with severe WMHs were further divided depending on whether a lacune was present. This phenotyping method overcomes the limitations of other classi cation methods in that it only counts the number of CSVD markers but does not consider their nature.…”
Section: Discussionmentioning
confidence: 99%
“…The first step of the stratification scheme differentiated CSVD into bleeding and nonbleeding subtypes. Bleeding CSVDs were further stratified into different subtypes with CMBs of specific topographic features that have distinct underlying microvasculopathy: strictly lobar CMBs considering as CAA and mixed CMBs as arteriosclerosis/lipohyalinosis microvasculopathy 14 , 15 . Regarding nonbleeding CSVDs, individuals with severe WMHs were further divided depending on whether a lacune was present.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral microbleeds increase the risk of spontaneous intracerebral hemorrhage (ICH), ischemic stroke, cognitive impairment, and gait disturbance ( 9 , 10 ). Two main sporadic forms of SVD present with CMBs: hypertensive arteriopathy (HA) and cerebral amyloid angiopathy (CAA).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lobar CMBs, like strictly lobar CMBs, could suggest CAA pathology ( 12 ). A mix of lobar with nonlobar CMBs can occur in HA, but a HA-CAA synergism could also be responsible for CMB pathogenesis, which implies an SVD spectrum ( 10 , 11 , 13 ).…”
Section: Introductionmentioning
confidence: 99%